2020
DOI: 10.1002/anie.201914798
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanistic Perspective on Plastically Flexible Coordination Polymers

Abstract: Mechanical flexibility in single crystals of covalently bound materials is a fascinating and poorly understood phenomenon. We present here the first example of a plastically flexible one‐dimensional (1D) coordination polymer. The compound [Zn(μ‐Cl)2(3,5‐dichloropyridine)2]n is flexible over two crystallographic faces. Remarkably, the single crystal remains intact when bent to 180°. A combination of microscopy, diffraction, and spectroscopic studies have been used to probe the structural response of the crystal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 54 publications
1
66
0
Order By: Relevance
“…Single crystals of (1) deform plastically across two crystallographic faces when exposed to three-point bending (Figure 1c-d). 9 The reported vibrational spectra indicated that no structural changes occur within the CP chains during bending. Instead, the high mosaicity which resulted from bending was ascribed to inter-CP chain distortions.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…Single crystals of (1) deform plastically across two crystallographic faces when exposed to three-point bending (Figure 1c-d). 9 The reported vibrational spectra indicated that no structural changes occur within the CP chains during bending. Instead, the high mosaicity which resulted from bending was ascribed to inter-CP chain distortions.…”
mentioning
confidence: 93%
“…No significant changes are observed in the electronic structure of the covalent Zn-Cl-Zn chain upon compression, ESI S3.4. Single crystals of (1) exhibit unmistakable plasticity during three-point bending Figure 1c-d. 9 In stark contrast, the HP response of (1) is fully reversible, even following compression to 9.34 GPa. During decompression the crystallographic unit cell relaxes along the same pressure-volume (p-V) path with no detectable hysteresis, Figure 2a-b.…”
mentioning
confidence: 99%
See 3 more Smart Citations